(untitled) (Eurasian Journal of Philology Science and Education, 2015)
This article describes a novel genre that continues to occupy a dominant place in our literary process, despite the innovative elements in terms of style and complexity of forms of writing and multilayered narrative structure. In connection with the task a brief history of the formation of the novel genre is given in the article. Taking into account the distinguishing features of the genre of the novel the attention is drawn to the fact that some researchers emphasize the development of the inner world of the hero of the novel, the change of his character and identity, they are interested in the possibilities of the moral and intellectual development of the individual, in the nature of his formation in collision with authoritarian norms and representations of the old world. Noting new variations and modifications of the novel genre, such as a novel of culture, an industrial novel, an urban romance, the novels «The White Hole» and «The Mammoth Tooth» by the Kazakh writer N. Verevochkin are chosen for the analysis. The central theme of both novels is a choice between life and death, the transience of life and immortality, a choice between peace and chaos. The principal feature of «genre content» of novels by N.Verevochkin allows to see the eternal values of life in the tragic chaos, to think about the meaning of life and the place of the hero in this life.The structure and composition of the novel as a genre saturated by mythological story reflect the connection of time and human relations. In general, the novels of this Kazakhstan’s writer are characterized by «encyclopedic» genre structure, unique peculiarities of genre forms.